Sex Disparity in Academic Rank and Industry Payments to Plastic Surgeons. Issue 2 (February 2020) - Ngaage, Ledibabari M.; Harris, Chelsea; Rosen, Carly; Ge, Shealinna; Kim, Cecelia; Rada, Erin M.; Manahan, Michele; Silverman, Ronald P.; Slezak, Sheri; Rasko, Yvonne M.
Abstract : Introduction: Despite increasing representation in surgery, women continue to lag behind men in important metrics. Little is known on how industry funding may also contribute to this ongoing disparity. This article seeks to quantify industry payments to academic plastic surgeons (APSs) by sex and examine the relationship between funding and academic achievement. Methods: We conducted a cross-sectional analysis of industry payments disbursed to APSs in 2017. Faculty were identified using departmental listings of Accreditation Council for Graduate Medical Education plastic surgery residency programs. Payments were identified via the Center for Medicare and Medicaid Services open payment database. Academic achievement was assessed using rank (eg, assistant professor), leadership designation (eg, division head), and Scopus H-index and then controlled for time in practice. Results: Of the 805 APSs, the majority were male (82% male vs 18% female, P < 0.0001). Significant sex differences emerged in average yearly industry contributions (men, US 3202, vs women, US 707; P < 0.0001). Across all academic ranks, men received significantly higher payments than women ( P < 0.0500). Men constituted 93% of full professors and were almost twice as likely to hold additional leadership positions compared with women (odds ratio, 1.82; P = 0.0143). After adjustment for time in practice, there was no difference in H-indices between male and female APSs, although payment disparity persisted ( P < 0.0001). Conclusions: Substantial sex-based disparities exist among APSs' academic rank and leadership attainment, which is not attributed to differences in academic qualifications or experience. To better elucidate the sources of this disparity, future studies should assess sexed differences in payment types. Furthermore, we urge for increased transparency in the selection process for industry payments.